2013
DOI: 10.21608/ejabf.2013.2155
|View full text |Cite
|
Sign up to set email alerts
|

Studies on fertilization sources with artificial feeds on productivity of earthen ponds stocked with different fish species

Abstract: The present study was carried out at a private fish farm at Tolombat 7 site Kafr El-Sheikh Governorate, Egypt. The study was performed for 140 days during the period from 5 Th July to 27 Th November 2010. The study aimed to investigate the effect of different fertilization and feeding systems on growth performance; feed and Nitrogen utilization; whole body chemical composition; water quality; plankton abundance; some blood parameters and economic evaluation of earthen ponds cultured with different fish species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 8 publications
3
7
0
Order By: Relevance
“…These results are in partial agreement with the finding of Abdel-Hakim et al (2013) who reported that DM contents in whole tilapia bodies ranged between 30.65 and 27.29%. Regarding the CP contents in tilapia whole bodies results of Table (10) indicate that CP contents of T 1 ; T 2 and T3 were 64.20 and 64.85 and 65.40%, respectively and T 3 showed significantly (P<0.05) higher CP contents in the DM compared to T 2 and T 1 .…”
Section: Whole Body Chemical Compositionsupporting
confidence: 93%
See 3 more Smart Citations
“…These results are in partial agreement with the finding of Abdel-Hakim et al (2013) who reported that DM contents in whole tilapia bodies ranged between 30.65 and 27.29%. Regarding the CP contents in tilapia whole bodies results of Table (10) indicate that CP contents of T 1 ; T 2 and T3 were 64.20 and 64.85 and 65.40%, respectively and T 3 showed significantly (P<0.05) higher CP contents in the DM compared to T 2 and T 1 .…”
Section: Whole Body Chemical Compositionsupporting
confidence: 93%
“…In this contents Abdel-Hakim et al (2013) reported higher values of ash contents in whole bodies of Nile tilapia which ranged between 10.36 and 11.74% and the ash values were significantly affected with type of fertilization with feeding. As presented in Table (10) averages of NFE contents in the DM of Nile tilapia whole bodies for T 1 ; T 2 and T 3 were 2.76; 1.88 and 1.10%, respectively and the statistical evaluation of NFE indicate that T 1 had significantly (P<0.05) the highest NFE records and followed in a significant (P<0.05) decreasing order by T 2 and T 3 , respectively.…”
Section: Whole Body Chemical Compositionmentioning
confidence: 59%
See 2 more Smart Citations
“…Results presented in Table (5) are also in agreement with the findings of Eid et al, (2009) who found that final weight, weight gain, specific growth rate, daily weight gain and gross yield of Nile tilapia were significantly higher received feed plus poultry manure plus urea and triple super phosphate compared to the ponds received feed only. In this respect Abdel- Hakim et al (2013) reported that growth performance parameters of Nile tilapia reared in polyculture ponds and the gross yield recorded significantly the highest values in ponds received artificial feed plus poultry manure and chemical fertilizers (urea + triple super phosphate) compared to ponds received feed only or feed plus poultry manure or feed plus inorganic fertilizers.…”
Section: Growth Performancementioning
confidence: 97%